Immigrant networks and their implications for occupational choice and wages - Krishna Patel; Francis Vella (Institute for the Study of Labor (IZA), 2007)
This paper employs United States Census data to study the occupational allocation of immigrants. The data reveal that the occupational shares of various ethnic groups have grown drastically in regional labor markets over the period 1980 to 2000. We examine the extent to which this growth can be attributed to network effects. That is, we examine the relationship between the occupational choice decision of recently arrived immigrants with those of established immigrants from the same country. We also consider the earnings implications of these immigrant networks for recent arrivals. The empirical evidence strongly suggests the operation of networks in the immigrant labor market. First, we find evidence that new arrivals are locating in the same occupations as their countrymen. Moreover, this location decision is operating at the level of regional labor markets. Second, we find that individuals who locate in the popular occupations of their countrymen enjoy a large and positive effect on their hourly wage and their level of weekly earnings.
Keywords: J24; 330; Network effects; immigrants; occupational choice; earnings; Migranten; Berufswahl; Lohnstruktur; Soziales Netzwerk; Regionaler Arbeitsmarkt; USA